(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to detect phenomenal treatments in the design of indoor spaces for event rooms and joys according to their performance effectiveness. In the light of the realization of changing formal values of the elements across them, the functional and aesthetic expressive aspect is done. In order to enforce the research objective, the researcher conducted a thorough study, which included three chapters, the first dealing with the problem of research and its relevance and purpose, as well as the limits and definition of terminology. Chapter II contained the theoretical framework, which in turn included researchers, the first of which took demonstrational treatments in indoor spaces. Then came the second research aesthetics of demonstrational treatments in indoor spaces and the employment of systems and design relationships, and then came up with a set of conclusions and recommendations. Keywords: interior space - hall design - interior design treatment - wedding halls - art design.